Collective Memories of WWII Collaboration in Belgium and Attitudes About Amnesty in the Two Main Linguistic Communities - Laura De Guissmé; Laurent Licata; Aurélie Mercy (Kultura (Skopje), 2014)
Collaboration with the Nazi occupier during WWII has always been a topic of dissent between French-speakers (FS) and Dutch-speakers (DS) in Belgium. According to a popular myth coined after the war and often narrated in the media and literature, collaboration was widespread in Flanders, whereas Walloons bravely resisted, although historical reality is much more nuanced. These representations regularly resurface in political debates surrounding the Belgian linguistic conflict. Demands for amnesty addressed by nationalist Flemish parties are a case in point. A questionnaire survey (N = 521; 315 FS and 206 DS) showed that collaboration was represented negatively and was morally condemned in both groups. However, DS expressed more Support for Amnesty (SA) than FS. This effect of Linguistic Group (LG) on SA was mediated by judgment of morality of collaboration, and this mediation was moderated by identification with the LG. Interestingly, SA was predicted by judgments of morality of DS, but not of FS, collaborators, in both groups, as if francophone collaboration was deemed irrelevant. Results suggest that differences between DS and FS in political position taking regarding the granting of amnesty are partly due to differences in representations of collaboration, and to different perspectives towards the same historical representation. The myth is both shared and disputed.